Strategic combination of feed additives aimed at manipulating ruminal kinetics and fermentation to increase energy efficiency and mitigate enteric methane emission and waste in ruminants - Sene, Guilherme Acácio de (2022)
This study aimed to evaluate the use of essential oils, exogenous enzymes, sodium monensin, and their associations as a nutritional strategy to mitigate ruminal CH4 emissions from Nellore cows and their impacts on the anaerobic biodigestion of manure. The thesis was structured in two studies. In study 1, eight cannulated Nellore cows (480 ± 55 kg) were used, distributed in a duplicated 4 x 4 Latin square design, in a 2 x 2 x 2 factorial scheme (4 periods of 28 days) totaling 4 repetitions (32 experimental units). The animals received a basal diet composed of 60% corn silage and 40% concentrate, with the daily supply being adjusted as a function of DMI. The factors were composed by the presence or absence of exogenous enzyme (1027 mg/kg DM), essential oil (31.7 mg/kg DM), and monensin (30.6 mg/kg DM) in the diet. Data were analyzed using SAS PROC MIXED and differences were declared significant at 5%. The association between the additives promoted alterations in the DMI, being antagonistic on the microbial efficiency, on the digestible energy lost in the form of ruminal CH4, and on the gross energy released in the intestine. However, no associative effects were observed between the additives on the production of SCFA. In study 2, experimental anaerobic batch-type biodigesters were used in a completely randomized design (32 experimental units) to evaluate the anaerobic biodigestion of waste from Nellore cows fed with sodium monensin, exogenous enzyme, essential oil, and their combinations. Data were also analyzed using SAS PROC MIXED and differences were declared significant at 5%. The association between the tested additives did not change the biodigestion process, however, the use of sodium monensin has been shown to reduce the biogas production potency and the concentration of nutrients in the biofertilizer. Thus, the association between the tested additives as a nutritional strategy did not prove to be able to reduce ruminal CH4 emissions, with no effect on the anaerobic biodigestion of manure.